Sanitary Practices of Street Food Vendors: A Cross-sectional Comparative Study, Lahore, 2023 (Journal of Fatima Jinnah Medical University, 2024)
Background: Street food is an important source of nourishment for many in urban areas. However, any compromise in hygienic practices can render it unsafe for human consumption. The objective of this study was to assess the sanitary practices of street food vendors and their relation to the sociodemographic profile, in LahoreSubjects and methods: This was a cross-sectional comparative study conducted in Lahore, Punjab for 6 months after ethical clearance. Street vendors from areas around Ameer ud Din Medical College, which are densely populated with a multitude of offices and hostels, were included in the study after informed consent. Convenience sampling and a predesigned questionnaire were used by the researchers to collect data from 288 vendors. Demographic variables and vending practices were studied and compared using chi-square test. For data entry and analysis SPSS version 23 was used.Results: The average age of the vendors was 34.6 years. 286 (99.3 %) were males,195 (67.7%) were married and 138 (47.9%) had vending experience of less than 5 years. 60 (21%) had education of graduate and above level. 209 (76%) had a monthly income below 50,000 rupees. 61 (21.2%) had a good vending practices score, i.e. a score of 75% and above based on water usage, usage of sanitary toilet facilities, hand washing and nearby environment of the vending site. There was no significant association between sanitary practices and sociodemographic variables.Conclusion: Most vendors did not have a good vending practices score. Sanitary practices of the vendors had no relation with gender, marital status, education, work experience or monthly income of the vendors.
Keywords: Sanitary practices, YBOC scale